IMPLEMENTASI KEBIJAKAN PENATAAN RUANG TERBUKA HIJAU - ', Hayat ' (Jurnal Ilmu Administrasi Negara, 2014)
Implementation of Planning Policy Green Open Space. This study aims todetermine the implementation of the arrangement of green open space (RTH) in Malang andits impact on the development of Malang City, was based Malang Regional Regulation No. 7Year 2001 on Spatial Planning Malang. Descriptive research method uses quantitative methods.Samples were taken as many as 40 people using purposive sampling technique. Techniques ofdata collection using questionnaires, interviews, and documentation. Data analysis techniquesused the frequency table generated from the source data taken using a percentage according tothe indicators evaluated. The results showed that the arr0angement of the Malang City greenopen space is still less appropriate to use, needs, grouping, management, and development. Theimplications of the research needed serious attention and good cooperation for memathui rulesand regulations associated with RTH. Need to be a maintenance and preservation of green spacewhere a growing number of community needs clean environment, healthy and comfortable.Keywords: spatial planning, urban green space, the implementation of the policy.